Amyloid-mediated remineralization for tooth hypoplasia of cleidocranial dysplasia - Guo, Xiaohe; Yang, Xiaoxue; Liu, Peisheng; Huang, Xiaoyao; Gu, Yang; Guo, Hao; Xuan, Kun; Liu, Anqi (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Cleidocranial dysplasia (CCD) is an autosomal-dominant, heritable skeletal and dental disease, involving hypoplastic clavicles, defective ossification of the anterior fontanelle, dentin and enamel hypoplasia, and supernumerary teeth, which can seriously affect the oral and mental health of patients. Amyloid-like protein aggregation, which is established by lysozyme conjugated with polyethylene glycol (Lyso-PEG), forms a mineralized nanofilm layer on a healthy enamel surface. However, whether it can form a remineralization layer in dental tissues from CCD remains unclear. Methods This study evaluated deciduous teeth from healthy individuals and a patient with CCD. Because pulp and dentin are functionally closely related, stem cells from human exfoliated deciduous teeth (SHED) from CCD patients and healthy individuals were collected to compare their biological properties. Results The results found that deciduous teeth from patients with CCD exhibited dentin hypoplasia. In addition, the proliferative ability and osteogenic potential of SHED from patients with CCD were lower than those of control individuals. Finally, Lyso-PEG was applied to dentin from the CCD and control groups, showing a similar remineralization-induced effect on the dentin surfaces of the two groups. Conclusion These results extend our understanding of the dentin and SHED of patients with CCD, exhibiting good caries-preventive capacity and good biocompatibility of Lyso-PEG, thus providing a novel dental therapy for CCD and patients with tooth hypoplasia.